Catalytic oxidative degradation method for polyolefin plastic

By acid-modifying the ZSM-5 molecular sieve catalyst to increase the acid sites and specific surface area, the problem of dependence on precious metals was solved, and the efficient and low-energy conversion of polyolefin plastics into dicarboxylic acids was achieved.

CN120923336APending Publication Date: 2025-11-11SHANGHAI UNIV (JIAXING ZHEJIANG) EMERGING IND RES INST
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510936820.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-08
Publication Date
2025-11-11

AI Technical Summary

Technical Problem

Existing catalytic systems rely on precious metals or complex hierarchical porous materials, resulting in high costs for the catalytic oxidation degradation of polyolefin plastics and making it difficult to achieve efficient and low-energy conversion into dicarboxylic acids.

Method used

Acid modification was performed using ZSM-5 molecular sieve catalyst with a Si/Al molar ratio of ≤38, and catalytic oxidation degradation was carried out in combination with specific process parameters to increase acid sites and specific surface area, thereby promoting the breaking of C-C bonds in polyolefin plastics.

Benefits of technology

It achieves a yield of over 70% for the catalytic oxidative degradation of liquid oil from polyolefin plastics, with a maximum yield of up to 94%, reducing energy consumption and providing a low-cost and high-efficiency catalytic oxidative cracking conversion scheme.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120923336A_ABST
    Figure CN120923336A_ABST
Patent Text Reader

Abstract

The invention relates to a method for catalytic oxidative degradation of polyolefin plastic, and belongs to the technical field of polyolefin plastic recovery. The method comprises the following steps: modifying a ZSM-5 molecular sieve catalyst with a set Si / Al molar ratio by using an acid with a set molar concentration to obtain a modified ZSM-5 molecular sieve catalyst; wherein the Si / Al molar ratio is set to be smaller than or equal to 38 and larger than 0; and mixing the modified ZSM-5 molecular sieve catalyst, polyolefin plastic and water, and carrying out a catalytic oxidation degradation reaction to obtain a reaction solution containing binary acid. According to the embodiment of the invention, the ZSM-5 molecular sieve is modified by acid, so that the pore structure of the ZSM-5 molecular sieve can be optimized, then in the catalytic reaction, the strong acid site after acid modification promotes C-C bond breakage of polyolefin, the yield of the degraded product liquid oil is improved, the yield is 70% or above, and meanwhile, the energy consumption and the cost of the catalytic oxidation degradation reaction are reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of polyolefin plastic recycling technology, and in particular to a method for catalytic oxidative degradation of polyolefin plastics. Background Technology

[0002] The demand for plastic products is increasing. As a widely used material, plastic brings convenience to life but also causes serious environmental pollution problems. The existing plastic waste treatment technology system mainly covers four technical paths: landfill disposal, incineration, physical recycling and chemical conversion: (1) Although the traditional landfill disposal method is simple to operate, it has problems such as high land resource occupation, high risk of leachate pollution and potential secondary environmental hazards; (2) Although the incineration energy utilization technology can realize energy recovery, it faces technical bottlenecks in the practical application of controlling the generation of persistent organic pollutants such as dioxins; (3) Although the physical recycling method (such as regeneration granulation) can maintain the material matrix characteristics, it has the inherent defect of significant material performance degradation after multiple cycles; (4) As an emerging conversion pathway, thermal pyrolysis chemical recycling technology can convert waste plastics into high-value-added energy products such as pyrolysis oil and syngas, but its industrial application is still constrained by technical and economic constraints such as high reaction energy consumption and difficulty in product selectivity control. It is worth noting that the global comprehensive recycling rate of plastic waste is still less than 10%, and the need for technological upgrading is urgent. Specifically for polyolefin plastics (such as PE and PP), which account for more than 60% of the composition, their molecular structure constitutes a significant degradation barrier: the high-energy C-C single bonds (bond energy approximately 347 kJ / mol) and CH bonds (bond energy approximately 413 kJ / mol) in the main chain form a stable framework structure, coupled with highly crystalline properties and chemically inert surface characteristics, resulting in extremely strong resistance to bio / chemical degradation in the natural environment. The combined effect of these characteristics and the limitations of recycling technologies presents the recycling of polyolefin plastics with dual thermodynamic and kinetic challenges.

[0003] In recent years, chemical upgrading and recycling technologies for polyolefins based on catalytic oxidation reactions have emerged as a new research direction to overcome the bottlenecks of traditional treatment methods. This technology, through an oxidative bond-breaking and functionalization pathway, can convert polyolefins into high-value chemicals such as carboxylic acids and ketones under mild conditions, offering both environmental and economic benefits. However, existing catalytic systems often rely on precious metal catalysts (such as Ru, Angew. Chem. Int. Ed. 2023, 62, e20230134) or require complex preparation processes using hierarchical porous materials (such as MCM-41, Angew. Chem. Int. Ed. 2024, 63, e202407510), resulting in high catalyst costs. Therefore, there is an urgent need to develop novel, inexpensive, and efficient catalytic materials to lower the technological application threshold and provide a more economically feasible solution for the high-value conversion of polyolefin waste. Summary of the Invention

[0004] This application provides a method for the catalytic oxidative degradation of polyolefin plastics to solve the following technical problem: how to achieve low cost and low energy consumption to improve the yield of polyolefin plastics catalytic oxidative cracking into dicarboxylic acids.

[0005] Treatment of catalysts improves the yield of liquid oil from the catalytic oxidative degradation of polyolefin plastics.

[0006] In a first aspect, embodiments of this application provide a method for the catalytic oxidative degradation of polyolefin plastics, the method comprising:

[0007] The ZSM-5 molecular sieve catalyst with a set Si / Al molar ratio is modified by using an acid with a set molar concentration to obtain a modified ZSM-5 molecular sieve catalyst; wherein the set Si / Al molar ratio is ≤38 and greater than 0.

[0008] The modified ZSM-5 molecular sieve catalyst, polyolefin plastic, and water were mixed to carry out a catalytic oxidative degradation reaction to obtain a reaction solution containing a dicarboxylic acid.

[0009] Optionally, the Si / Al molar ratio is set to 25–38.

[0010] Optionally, the set molar concentration is 0.03 mol / L to 0.23 mol / L.

[0011] Optionally, the ratio of the volume V of the acid to the mass M of the ZSM-5 molecular sieve catalyst is (30-70):(0.2-2), where V is in ml and M is in g.

[0012] Optionally, the acid includes at least one of the following: inorganic acid and organic acid.

[0013] Optionally, the inorganic acid includes at least one of the following: hydrochloric acid, nitric acid, phosphoric acid; and / or,

[0014] The organic acid includes at least one of the following: citric acid and oxalic acid.

[0015] Optionally, the modification process parameters include: a temperature of 70℃~90℃ and a time of 0.5h~1.5h.

[0016] Optionally, the process parameters for the catalytic oxidation degradation reaction include: air pressure of 1 MPa to 2 MPa, temperature of 140°C to 170°C, and time of 4 h to 14 h.

[0017] Optionally, the modified ZSM-5 molecular sieve catalyst is used in a mass ratio of 1:4 to 2:1 to the polyolefin plastic.

[0018] Optionally, the polyolefin plastic includes at least one of the following: high-density polyethylene, linear low-density polyethylene, low-density polyethylene, polypropylene plastic, and finished polyolefin plastics.

[0019] The technical solutions provided in this application have the following advantages compared with the prior art:

[0020] The method for catalytic oxidative degradation of polyolefin plastics provided in this application uses ZSM-5 molecular sieve, a non-precious metal with a Si / Al molar ratio ≤38 and >0, as a catalyst. This catalyst has high acidity, resulting in rapid oxidative cracking of polyolefin plastics. Furthermore, acid modification of the ZSM-5 molecular sieve increases its acidic sites and specific surface area. In subsequent catalytic reactions, the strong acidic sites and pore structure of the acid-modified ZSM-5 molecular sieve promote polyolefin diffusion and C / C bond breaking, thereby increasing the yield of liquid oil, a product of the catalytic oxidative degradation of polyolefin plastics, to over 70%, and up to 94% or more. Simultaneously, it reduces the energy consumption of the catalytic oxidative degradation reaction. In summary, by acid-modifying the inexpensive ZSM-5 molecular sieve catalyst, a low-cost and low-energy-consumption method is achieved to increase the yield of polyolefin plastics converted into dicarboxylic acids through catalytic oxidative cracking. Attached Figure Description

[0021] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with this application and, together with the description, serve to explain the principles of this application.

[0022] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0023] Figure 1 A schematic flowchart illustrating a method for the catalytic oxidative degradation of polyolefin plastics provided in this application embodiment;

[0024] Figure 2 This application provides a reaction formula for a method of catalytic oxidative degradation of polyolefin plastics.

[0025] Figure 3 An infrared spectrum of ZSM-5 (Si / Al=25) provided for an embodiment of this application;

[0026] Figure 4 Infrared spectrum and NMR spectrum of the liquid oil product from the catalytic oxidative degradation method for polyolefin plastics provided in Example 3 of this application. 1H-spectrum; where: a-infrared spectrum, b-NMR spectrum 1 H spectrum;

[0027] Figure 5 This is a high-resolution mass spectrum of the product of a method for catalytic oxidative degradation of polyolefin plastics provided in Example 7 of this application;

[0028] Figure 6 The graph shows the liquid oil mass / initial PE mass after treatment with different acid concentrations in a method for catalytic oxidative degradation of polyolefin plastics provided in this application embodiment. Detailed Implementation

[0029] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.

[0030] Various embodiments of this application may exist in the form of a range; it should be understood that the description in the form of a range is merely for convenience and brevity and should not be construed as a hard limitation on the scope of this application; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values ​​within that range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., and single numbers within the range, such as 1, 2, 3, 4, 5, and 6, regardless of the range. Furthermore, whenever a numerical range is referred to herein, it means including any referenced number (fraction or integer) within the referred range.

[0031] In this application, unless otherwise stated, directional terms such as "upper" and "lower" specifically refer to the drawing directions in the accompanying drawings. Furthermore, in the description of this application, terms such as "comprising" and "including" mean "including but not limited to." In this document, relational terms such as "first" and "second" are used merely to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. In this document, "and / or" describes the relationship between related objects, indicating that three relationships can exist; for example, A and / or B can represent: A alone, A and B simultaneously, or B alone. A and B can be singular or plural. In this document, "at least one" means one or more, and "more than one" means two or more. "At least one," "at least one of the following," or similar expressions refer to any combination of these items, including any combination of single or plural items. For example, "at least one of a, b, or c" or "at least one of a, b, and c" can both represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple. "Parts representation" such as parts by weight or parts by mass indicates the proportional relationship between components. In the proportional relationships discussed in this article, parameters that need to be described by proportion should be understood as the first term of the proportion in the order of description, while the proportion figure should be understood as the second term. For example, if the mass ratio of substance A, substance B, and substance C is 1:2:3, then substances A, B, and C should correspond one-to-one with the proportion figure in the proportion in the order of description, i.e., the mass of substance A : the mass of substance B : the mass of substance C = 1:2:3.

[0032] Unless otherwise specified, all raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.

[0033] In a first aspect, embodiments of this application provide a method for the catalytic oxidative degradation of polyolefin plastics. Figure 1 A schematic flowchart of a method for catalytic oxidative degradation of polyolefin plastics provided in this application embodiment; please refer to... Figure 1 The method includes:

[0034] S1. Modify the ZSM-5 molecular sieve catalyst having a set Si / Al molar ratio using an acid with a set molar concentration to obtain a modified ZSM-5 molecular sieve catalyst; wherein the set Si / Al molar ratio is ≤38 and greater than 0.

[0035] ZSM-5 molecular sieves possess a unique pore structure and a high silica-to-alumina ratio, exhibiting excellent thermal stability, acid resistance, and selective catalytic performance. This is primarily attributed to their special pore structure and physicochemical properties. Their crystal structure belongs to the orthorhombic system, featuring two intersecting pore systems: one is a cylindrical pore system, and the other is a "Z"-shaped transverse pore system. This provides the molecular sieve with excellent diffusion properties and shape-selective catalytic characteristics. ZSM-5 molecular sieves are materials with highly selective catalytic activity, and their pore structure has a significant impact on catalytic reactions. ZSM-5 molecular sieves have two main pore structures: 1. A zigzag pore with an elliptical cross-section, approximately 0.51 × 0.55 nm in size, opening at the 100 facet of the molecular sieve particle. 2. Another type of pore with a nearly circular cross-section, approximately 0.53 × 0.56 nm in size, is a through-hole pore opening at the 010 facet of the molecular sieve particle.

[0036] The Si / Al molar ratio of ZSM-5 molecular sieve refers to the molar ratio of silica (SiO2) to alumina (Al2O3) in the molecular sieve framework. The Si / Al molar ratio indicates the surface acidity of the ZSM-5 molecular sieve; a higher Si / Al molar ratio indicates lower acidity. During the synthesis of this type of molecular sieve, the increased aluminum content may lead to the formation of non-framework aluminum, which affects the microstructure, crystallinity, and pore structure of the molecular sieve. With an increased Si / Al ratio, the crystallinity and structural regularity of the molecular sieve improve, and the particle size distribution becomes more uniform. Furthermore, the Si / Al ratio also affects the pore structure; specifically, with an increased Si / Al ratio, the BET specific surface area, external specific surface area, and pore volume all increase. Subsequent combinations with other reaction conditions allow for the directional control of the structure and molecular chain length of the main reaction products, significantly improving the liquid oil mass / initial PE mass ratio of high-value-added dicarboxylic acids.

[0037] In this embodiment, a non-precious metal ZSM-5 molecular sieve with a Si / Al molar ratio ≤38 and greater than 0 is used as the catalyst. This catalyst has high acidity, resulting in rapid oxidative cracking of polyolefin plastics. Furthermore, modifying the ZSM-5 molecular sieve with acid can further increase the acidic sites, increase the specific surface area, and optimize the pore structure of the ZSM-5 surface. If the Si / Al molar ratio is higher than 38, the framework aluminum content is low (Al percentage <2.6%), making it difficult for acid to further remove the framework aluminum (requiring strong acid or high temperature conditions). High Si / Al ratio molecular sieves reduce acidic sites and decrease the carbon deposition rate, but at the cost of a significant decrease in catalytic activity, requiring compensation by increasing the temperature (+30-50℃), leading to increased energy consumption. For example, a ZSM-5 molecular sieve with Si / Al = 25 not only has a regular pore structure but also very strong acidic sites. The density of these acidic sites is generated by Al species in the catalyst composed of silica and alumina. Therefore, we can change the surface acidity and structural characteristics of the ZSM-5 molecular sieve by adjusting the acid concentration.

[0038] Acid modification has two main effects on molecular sieves: one is to increase the number of acid sites, and the other is to increase the specific surface area. The main technical effect is to improve the reaction rate. The mechanism of the increased reaction rate is that carbocations are formed, which is conducive to the activation and breaking of C-C bonds and the occurrence of subsequent oxidation reactions.

[0039] In some embodiments, the Si / Al molar ratio is set to 25–38.

[0040] For example, the Si / Al molar ratio can be set to 25, 27, 29, 30, 31, 33, 35, 37, 38, etc.

[0041] In some embodiments, the set molar concentration is 0.03 mol / L to 0.23 mol / L.

[0042] The molar concentration can be set between 0.03 mol / L and 0.18 mol / L to ensure adequate dealumination of the acid-modified ZSM-5 framework. If the set molar concentration is higher than 0.23 mol / L, it may lead to excessive dealumination of the ZSM-5 framework, causing the collapse of the silicon-oxygen tetrahedron (SiO4) structure and severely weakening the catalyst stability. Conversely, if the set molar concentration is lower than 0.03 mol / L, insufficiently dealumination of ZSM-5 may lead to excessive cracking due to the high acid density, generating small molecule gases instead of the target liquid product. For example, the set molar concentration can be 0.03 mol / L, 0.06 mol / L, 0.08 mol / L, 0.10 mol / L, 0.12 mol / L, 0.14 mol / L, 0.16 mol / L, 0.18 mol / L, 0.2 mol / L, 0.23 mol / L, etc.

[0043] In some embodiments, the ratio of the volume V of the acid to the mass M of the ZSM-5 molecular sieve catalyst is (30-70):(0.2-2), where V is in ml and M is in g.

[0044] The ratio of acid volume V to the mass M of the ZSM-5 molecular sieve catalyst can be (30-70):(0.2-2) to ensure that the acid solution fully wets the catalyst particles, uniformly etches the non-framework aluminum, and avoids excessive acid damaging the framework structure. This acid dosage can reduce waste liquid treatment costs, and the treated catalyst can maintain high activity without complex regeneration, making it suitable for industrial scale-up. For example, the ratio of acid volume V to the mass M of the ZSM-5 molecular sieve catalyst can be 30:0.2, 70:2, 40:1, 50:1.5, 60:0.5, 45:0.8, etc.

[0045] In some embodiments, the acid includes at least one of the following: inorganic acid and organic acid.

[0046] In some embodiments, the inorganic acid includes at least one of the following: hydrochloric acid, nitric acid, phosphoric acid; and / or, the organic acid includes at least one of the following: citric acid, oxalic acid.

[0047] The acid can be inorganic or organic. Inorganic acids can be one or more combinations of hydrochloric acid, nitric acid, and phosphoric acid, while organic acids can be one or two of citric acid and oxalic acid. The technical principle of acid-modified ZSM-5 molecular sieves is as follows: Enhanced acidic sites: Acid modification (such as hydrochloric acid) increases the number of Brønsted acid sites (protic acids) and Lewis acid sites (aprotic acids) by dealumination (Al) or adjusting the framework silicon-aluminum ratio, thereby improving catalytic activity, especially in reactions such as cracking and isomerization. The silanol groups (Si-OH) formed after dealumination can further optimize the acidic distribution and enhance the directed catalytic ability for specific reactions. Optimized pore structure: Acid modification dissolves some amorphous impurities or blockages, clearing micropores (0.5-0.6 nm) and mesopores, improving mass transfer efficiency, and making it easier for reactant molecules to diffuse to active sites. Partial dealumination may form secondary mesoporous structures (such as "dealuminization mesoporization"), increasing the effective specific surface area and accessible active sites. Stability enhancement: Acid modification can remove skeletal defects, strengthen structural integrity, improve thermal stability (such as resistance to high-temperature coking) and hydrothermal stability, improve the selectivity of catalytic reactions, reduce carbon deposit deactivation, and extend catalyst life.

[0048] In some embodiments, the modification process parameters include: a temperature of 70℃~90℃ and a time of 0.5h~1.5h. These parameters ensure uniform acid modification and control over the degree of dealuminization. The 70℃~90℃ temperature ensures sufficient acid penetration into the molecular sieve, preventing localized over-acidification that could lead to structural collapse. Stirring can be performed during the modification process to promote mass transfer, ensuring uniform dealuminization and impurity dissolution, reducing structural defects after acid modification. Compared to high-temperature treatment (e.g., above 100℃), the 70℃~90℃ low-temperature method reduces energy consumption while maintaining processing efficiency, making it suitable for large-scale production. The 0.5h~1.5h time achieves gentle dealuminization, preventing excessive dealuminization that could lead to skeletal collapse or loss of acid sites. For example, the temperature can be 70℃, 72℃, 74℃, 76℃, 78℃, 80℃, 82℃, 84℃, 86℃, 88℃, 90℃, etc.; the time can be 0.5h, 0.7h, 0.9h, 1.0h, 1.2h, 1.4h, 1.5h, etc.

[0049] S2. The modified ZSM-5 molecular sieve catalyst, polyolefin plastic and water are mixed to carry out a catalytic oxidation degradation reaction to obtain a reaction solution containing dibasic acid.

[0050] The effects of the acid-modified ZSM-5 molecular sieve catalyst on polyolefin plastics include: catalytic cracking: the acid-modified strong acid sites promote the breaking of C-C bonds in polyolefins (such as polyethylene and polypropylene), reducing the energy consumption of cracking. Inhibition of coking: the optimized acidity distribution reduces excessive aggregation of strong acid sites, lowers the coking rate, and extends catalyst lifetime. The presence of mesopores allows coke precursors to diffuse rapidly away from the active sites, delaying deactivation.

[0051] If ZSM-5 molecular sieves are not acid-modified, the following will occur: Insufficient acidity: Natural or untreated ZSM-5 may have a low silica-alumina ratio and weak acidity, resulting in low catalytic cracking efficiency (such as a 30-50% decrease in conversion rate), requiring higher temperatures or longer time.

[0052] Specifically, ZSM-5 molecular sieves with a Si / Al molar ratio ≤38, based on the strong acidity of their surface, under the aforementioned reaction conditions, firstly, the interaction of acidic sites on the molecular sieve may occur. Polyethylene molecules initially interact with acidic sites (such as Brønsted acid sites) on the molecular sieve surface, leading to the activation of the polyethylene molecules. Then, through a protonation process, carbocation intermediates are formed. Four types of β-splitting produce shorter carbocations and ortho- and iso-alkenes, which are further oxidized to alcohols, ketones, and acids. Alternatively, under the influence of acidic sites, the CH bonds in the polyethylene molecules may break, generating alkyl radicals. These alkyl radicals react with oxygen to form peroxide radicals. These peroxide radicals further react with other radicals in the polyethylene molecules, leading to the breaking of C / C bonds and the formation of oxidation products. The oxidation reaction is typically a chain reaction process, with the generation and consumption of radicals continuously occurring until the reaction reaches equilibrium. During oxidation, after the C / C bonds break, the generated intermediates are further oxidized to form carboxyl groups. For example, the formation of dicarboxylic acids can be promoted at low temperatures using gradient temperature control methods. By controlling the concentration of the catalyst acid and the time, the molecular chain length and structure of the product can be controlled, so that the product is mainly converted into a liquid dicarboxylic acid.

[0053] After the above reaction is completed, a reaction solution containing a dicarboxylic acid is obtained. The reaction solution includes liquid, gaseous, and solid products from PE pyrolysis. The liquid product (liquid oil) from PE pyrolysis is a liquid low-molecular-weight fatty carboxylic acid (dicarboxylic acid). The yield of the liquid product is calculated as: (mass of liquid product / mass of original polyolefin) × 100%.

[0054] In some embodiments, the process parameters of the catalytic oxidation degradation reaction include: an air pressure of 1 MPa to 2 MPa, a temperature of 140°C to 170°C, and a time of 4 h to 14 h.

[0055] By modifying the ZSM-5 catalyst with acid, the catalytic performance of ZSM-5 is improved and the reaction time is reduced. Under mild reaction conditions—air pressure of 1 MPa–2 MPa, temperature of 140°C–170°C, and time of 4–14 hours—polyethylene (PE) plastic can be directionally decomposed into high-value-added dicarboxylic acids. For example, the air pressure can be 1 MPa, 1.2 MPa, 1.4 MPa, 1.6 MPa, 1.8 MPa, 2 MPa, etc.; the temperature can be 140°C, 145°C, 150°C, 155°C, 160°C, 165°C, 170°C, etc.; and the time can be 4 hours, 6 hours, 8 hours, 10 hours, 12 hours, 14 hours, etc.

[0056] In some embodiments, the modified ZSM-5 molecular sieve catalyst is used in a mass ratio of 1:4 to 2:1 to the polyolefin plastic.

[0057] The mass ratio of modified ZSM-5 molecular sieve catalyst particles to polyolefin plastic can be 1:4 to 2:1. This ensures sufficient contact between the acidic sites on the catalyst surface and the polyolefin molecules, avoiding a local "covering" effect (active sites being obscured by macromolecules) caused by excessive plastic, thereby improving the catalytic efficiency per unit mass. If the mass ratio is lower than 1:4, the acidic sites cannot fully cover the polyolefin molecules, leading to incomplete cracking reactions (e.g., conversion rate drops from 85% to below 50%), leaving a large amount of unreacted plastic or waxy long-chain hydrocarbons, resulting in insufficient catalytic activity; and the catalyst's ability to regulate secondary reactions of intermediate products is weak, with products tending towards long-chain alkanes or uncracked residues, reducing the proportion of high-value dicarboxylic acid products. If the mass ratio is higher than 2:1, catalyst particle accumulation may lead to increased viscosity of the reaction system, decreased mass transfer efficiency (requiring higher stirring intensity or temperature compensation), increased difficulty in subsequent catalyst and residue separation, and increased energy consumption. For example, the mass ratio of the modified ZSM-5 molecular sieve catalyst to the polyolefin plastic can be 1:4, 1:3, 1:2, 1:1, 2:3, 2:1, etc.

[0058] In some embodiments, the polyolefin plastic includes at least one of the following: high-density polyethylene, linear low-density polyethylene, low-density polyethylene, polypropylene plastic, and finished polyolefin plastics.

[0059] Polyolefin plastics can be one or more of the following: high-density polyethylene (HDPE), linear low-density polyethylene (LLDPE), low-density polyethylene (LDPE), polypropylene plastic (PP), and polyolefin plastics.

[0060] This application provides a method for the catalytic oxidative degradation of polyolefin plastics, which has the following advantages:

[0061] (1) In the catalytic oxidation degradation reaction, the degradation process of polyolefin molecules on ZSM-5 molecular sieves involves adsorption, depolymerization, and desorption. Due to its unique pore structure and acidic properties, ZSM-5 molecular sieves exhibit carbocation or free radical mechanisms. The higher the concentration of acid-modified ZSM-5, the higher the catalyst specific surface area, which first increases and then decreases, leading to enhanced catalytic activity. The better the catalytic activity, the more olefins are generated. When the acidity is too high, the acid yield decreases, which may be related to the surface carbon. In summary, the acid-modified concentration promotes the cracking of polyolefins into olefins by ZSM-5 molecular sieve catalysts, converting them into dicarboxylic acids, and promoting the reaction process of polyolefin cracking into olefins.

[0062] (1) By acid-modifying ZSM-5 catalyst particles, the catalytic performance of ZSM-5 is improved and the reaction time is reduced. Under mild reaction conditions, it can directionally decompose polyethylene (PE) plastic into high-value-added dicarboxylic acids, making the yield of liquid oil stable at over 70% and the maximum yield up to 94%. It also optimizes reaction conditions and reduces overall energy consumption, providing a new and efficient strategy for the recycling of polyethylene waste plastics, and can meet the industrial recycling needs of high-value-added polyolefin plastics such as PE.

[0063] The present application is further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the application. Experimental methods in the following embodiments that do not specify specific conditions are generally determined according to national standards. If there is no corresponding national standard, then generally accepted international standards, conventional conditions, or conditions recommended by the manufacturer are followed.

[0064] Example 1

[0065] A method for catalytic oxidative degradation of polyolefin plastics includes:

[0066] (1) Prepare 50 ml of 0.03 mol / L hydrochloric acid solution, add 1 g of ZSM-5 molecular sieve (Si / Al=25) catalyst particles to the acid solution, stir at 80℃ for 1 h in a magnetic stirrer, filter the dispersion and wash it 5 times with deionized water; put the solid on the filter paper into an oven to dry, and then put it into a muffle furnace to be treated at 100℃ for 1 h, and let it cool to room temperature naturally;

[0067] (2) ZSM-5 (Si / Al = 25) catalyst particles, HDPE particles, and deionized water were added to a quartz tube reactor to obtain a dispersion of the catalyst and HDPE particles. Specifically, 0.1g of the acid-modified ZSM-5 catalyst particles, 0.2g of HDPE particles, and 15mL of H2O were added to the quartz tube reactor.

[0068] (3) Transfer the quartz tube reactor to the high-pressure reactor, fill it with high-purity air at a pressure of 1.5MPa, stir at 300r, increase the temperature at 5℃ / min, and maintain the reaction time for 8h after reaching 160℃. In one step, HDPE is directly converted into liquid dicarboxylic acid product through conversion directional reaction. Figure 2 This application provides a reaction formula for a method of catalytic oxidative degradation of polyolefin plastics; please refer to [link to relevant documentation]. Figure 2 For example, 0.2g of PE and 0.1g of hydrochloric acid-modified ZSM-5 molecular sieve catalyst particles with a silicon-to-aluminum ratio of 25 can be used as the reaction solvent in 15mL H2O. The reaction is carried out at 1.5MPa Air, 160℃ and 8h to generate a dicarboxylic acid product.

[0069] (4) After the reaction is complete, wait for the reactor to cool to room temperature before proceeding with post-processing. First, collect the gas using a gas bag, clean the quartz reactor with a mixture of ethanol and dichloromethane, collect the solid and liquid obtained from the reaction by filtration, and pass the liquid through a rotary evaporator to obtain a brownish-yellow oily liquid. The product is mainly a liquid oil.

[0070] Figure 3 An infrared spectrum of ZSM-5 (Si / Al=25) particles provided for an embodiment of this application; please refer to [link / reference]. Figure 3 Lattice vibration peaks: in the range of 400-750 cm⁻¹ -1 The characteristic peaks within this range mostly originate from lattice vibrations of the Si-O-Si ternary ring structure. The methyl peak is located at 3000 cm⁻¹. -1 The peaks appearing on the left and right sides are likely due to methyl groups in the template agent. (At 530-600 cm⁻¹) -1 Within the specified range, ZSM-5 zeolite exhibits a strong absorption peak, which is crucial for the stability of the ZSM-5 zeolite crystal framework. Si-O-Al symmetric stretching vibration: at 800 cm⁻¹ -1 The peaks appearing on the left and right may be due to the Si-O-Al symmetric stretching vibration. Characteristic peak of the pentagonal ring: at 550 cm⁻¹. -1 The peaks appearing on the left and right may be characteristic peaks of a five-membered ring. Hydroxyl group infrared peak: 3000-3800 cm⁻¹ -1 The infrared spectrum of hydroxyl (OH) groups in ZSM-5 molecular sieves within the specified range, with the peak at 3600 cm⁻¹. -1 There is an IR band at that location.

[0071] Example 2

[0072] Based on the disclosure in Example 1, Example 2 differs from Example 1 in that the molar concentration of the acid is 0.06 mol / L.

[0073] Example 3

[0074] Based on the disclosure in Example 1, Example 3 differs from Example 1 in that the molar concentration of the acid is 0.10 mol / L.

[0075] The yellow liquid product obtained in Example 3 was subjected to NMR and IR detection to characterize the product structure, and the product was inferred using high-resolution mass spectrometry. Figure 4 Infrared spectrum and NMR spectrum of the dicarboxylic acid produced by the catalytic oxidative degradation method of polyolefin plastics provided in Example 3 of this application. 1 H-spectrum; where: a-infrared spectrum, b-NMR spectrum 1 H spectrum; please refer to Figure 4 This indicates that in Figure 4In the 1H NMR spectrum of b, there is a distinct active hydrogen peak around 12 ppm. Figure 4 1715 cm⁻¹ in the infrared spectrum -1 The presence of carbonyl group characteristic peaks nearby indicates that the oily liquid product contains carboxylic acids. Specifically, according to... Figure 4 α-Associated carboxylic acids: Due to intermolecular hydrogen bonding, the OH stretching vibration peak shifts to lower wavenumbers, appearing in the 3200-2500 cm⁻¹ range. -1 Typically, the peaks are broad and diffuse; the CO stretching vibration peak usually appears at 1300-1200 cm⁻¹. - 1; Associated carboxylic acids: Due to hydrogen bonding, the C=O stretching vibration peak shifts to 1725-1700 cm⁻¹. -1 The characteristic peak of carboxylates, symmetric stretching vibration, appears at 1420-1300 cm⁻¹. -1 CH stretching vibration: asymmetric stretching vibration: occurs at approximately 2962 cm⁻¹ -1 Approximately 1375cm -1 Characteristic absorption peaks of methyl groups may also appear at this location. According to... Figure 4 The b-mass spectrum showed a carboxylic acid peak -COOH around 12 ppm.

[0076] Example 4

[0077] Based on the disclosure in Example 1, Example 4 differs from Example 1 in that the molar concentration of the acid is 0.14 mol / L.

[0078] Example 5

[0079] Based on the disclosure in Example 1, Example 5 differs from Example 1 in that the molar concentration of the acid is 0.18 mol / L.

[0080] Example 6

[0081] Based on the disclosure in Example 1, Example 6 differs from Example 1 in that the polyolefin plastic is PP plastic and the molar concentration of the acid is 0.10 mol / L.

[0082] Example 7

[0083] Based on the content disclosed in Example 1, Example 7 differs from Example 1 in that the polyolefin plastic is a SF Express packaging bag and the molar concentration of the acid is 0.10 mol / L.

[0084] Figure 5 This is a high-resolution mass spectrum of the dicarboxylic acid produced by a method for the catalytic oxidative degradation of polyolefin plastics provided in Example 7 of this application; please refer to... Figure 5This indicates that the mass spectrum of the liquid product was obtained by GC-MS testing. The chain length of the liquid product is distributed in C6-C21 dicarboxylic acids, thus obtaining long-chain dicarboxylic acids.

[0085] Example 8

[0086] Based on the disclosure in Example 1, Example 8 differs from Example 1 in that: ZSM-5 (Si / Al = 38) has an acid molar concentration of 0.03 mol / L.

[0087] Example 9

[0088] Based on the disclosure in Example 1, Example 9 differs from Example 1 in that: ZSM-5 (Si / Al = 38) has an acid molar concentration of 0.06 mol / L.

[0089] Example 10

[0090] Based on the disclosure in Example 1, Example 10 differs from Example 1 in that: ZSM-5 (Si / Al = 38) has an acid molar concentration of 0.10 mol / L.

[0091] Example 11

[0092] Based on the disclosure in Example 1, Example 11 differs from Example 1 in that: ZSM-5 (Si / Al = 38) has an acid molar concentration of 0.23 mol / L.

[0093] Example 12

[0094] Based on the disclosure in Example 1, Example 12 differs from Example 1 in that the molar concentration of the acid is 0.10 mol / L and the reaction time is 14 h.

[0095] Comparative Example 1

[0096] Based on the disclosure in Example 1, Comparative Example 1 differs from Example 1 in that the reaction time is 4 hours and there is no acid modification.

[0097] Comparative Example 2

[0098] Based on the content disclosed in Example 1, Comparative Example 2 differs from Example 1 in that the reaction time is 6 hours and there is no acid modification.

[0099] Comparative Example 3

[0100] Based on the disclosure in Example 1, Comparative Example 3 differs from Example 1 in that the original catalyst without acid modification is added to the reaction.

[0101] Comparative Example 4

[0102] Based on the disclosure in Example 1, Comparative Example 4 differs from Example 1 in that it contains unmodified and unheated ZSM-5 (Si / Al = 25) catalyst particles.

[0103] Figure 6 This application provides a method for the catalytic oxidative degradation of polyolefin plastics, showing yield diagrams after treatment with different acid concentrations; please refer to [link to relevant documentation]. Figure 6 Examples 1-5 and Comparative Example 4 show the liquid oil yields after treatment with different acid concentrations: 0.00 mol / L (representing 1 hour of water bath heating at 80°C without hydrochloric acid solution), 0.04 mol / L, 0.06 mol / L, 0.10 mol / L, 0.14 mol / L, and 0.18 mol / L hydrochloric acid solutions, over 8 hours. The corresponding liquid yields were 57%, 72%, 82%, 94%, 88%, and 71%, respectively, with the highest yield reaching 94% at 0.1 mol / L.

[0104] Comparative Example 5

[0105] Based on the disclosure in Example 1, Comparative Example 5 differs from Example 1 in that it has no catalyst.

[0106] Comparative Example 6

[0107] Based on the disclosure in Example 1, Comparative Example 6 differs from Example 1 in that air is replaced with nitrogen and the acid concentration is 0.10 mol / L.

[0108] Comparative Example 7

[0109] Based on the disclosure in Example 1, Comparative Example 7 differs from Example 1 in that the acid concentration is 0.10 mol / L and the reaction time is 6 h.

[0110] Comparative Example 8

[0111] Based on the disclosure in Example 1, Comparative Example 8 differs from Example 1 in that it contains ZSM-5 (Si / Al = 38) particles with an acid concentration of 0.26 mol / L.

[0112] The main reaction parameters and products of Examples 1-11 and Comparative Examples 1-7 are shown in Table 1.

[0113] Table 1

[0114]

[0115]

[0116] As shown in Table 1, by using ZSM-5 molecular sieve catalyst particles with a silicon-to-aluminum ratio of 25 to 38, introducing specific air pressure, setting acid modification concentration, temperature, and different PE plastics, and within the reaction time range set in the program, the catalytic oxidation cracking reaction process and mechanism can be synergistically controlled to achieve the goal of directional acquisition and maintenance of high yield of dicarboxylic acids.

[0117] The BET surface area, pore volume, and average pore size of the BJH adsorption of ZSM-5 molecular sieve catalyst (Si / Al=25) particles were tested. Please refer to Table 2 for the BET surface area of ​​ZSM-5 molecular sieve catalyst (Si / Al=25).

[0118] Table 2

[0119] Processing conditions BET surface area Original catalyst <![CDATA[309.2m 2 / g]]> Heating, acid-free modification <![CDATA[300.6m 2 / g]]> 0.03 mol / L <![CDATA[325.4m 2 / g]]> 0.10 mol / L <![CDATA[338.3m 2 / g]]> 0.18 mol / L <![CDATA[326.2m 2 / g]]>

[0120] Table 2 shows that the BET surface area of ​​the catalyst increases with increasing acid treatment concentration, but decreases when the acid treatment concentration reaches a certain value. Initial increase: Hydrochloric acid treatment first dissolves non-framework impurities (such as amorphous silica-alumina species) or some framework aluminum in the molecular sieve, clearing pores and exposing more internal surfaces, thereby increasing specific surface area and pore volume. Moderate acid concentration may introduce mesopores, improving mass transfer efficiency, especially beneficial for the diffusion and contact of active sites in macromolecular plastics (such as polyethylene and polypropylene). Initial surface cleaning and pore opening expose more active sites (such as acidic or metal sites), enhancing catalytic activity. Later decrease: Excessive acid treatment leads to framework structure destruction (such as excessive dealumination or framework collapse), reducing microporous structure, and causing some pores to collapse, resulting in a decrease in total surface area, possibly accompanied by the formation of mesopores.

[0121] One or more technical solutions in the embodiments of this application have at least the following technical effects or advantages:

[0122] (1) Using ZSM-5 molecular sieve with a non-precious metal and a Si / Al ratio of 25 as a catalyst, it can decompose polyethylene (PE) plastic into high-value dicarboxylic acid under mild reaction conditions, so that the yield of liquid oil is stable at more than 70% and can reach more than 94% at its highest. By continuously optimizing reaction conditions, reducing the overall energy consumption of the reaction, improving the economic performance of polyolefin recycling, exploring new and effective strategies, and realizing the industrial recycling demand for high-value PE plastic recycling products.

[0123] (2) Under the same time, the yield of liquid oil is increased. Compared with the unmodified ZSM-5 (silicon-aluminum ratio 25), the yield of liquid products is increased by the acid-modified catalyst, indicating that the catalyst’s catalytic performance is improved. This treatment method has a significant effect on the degradation of polyethylene (PE). Therefore, the reaction time can be shortened by acid-modifying the catalyst, thereby improving the economic benefits of recycling.

[0124] (3) A series of different acid concentrations were used to treat the ZSM-5 molecular sieve catalyst, and the solution concentration was changed to explore the effect of ZSM-5 molecular sieve on the oxidative pyrolysis and recycling of PE plastic particles under different concentration conditions. The optimal acid modification concentration was obtained by comparing the reaction results. Deionized water was used as the reaction medium, and the reaction was carried out at a temperature of 160℃ and an air pressure of 1.5MPa in the reactor. The PE plastic particles were directly catalytically oxidized into high-value dicarboxylic acids in one step. Compared with other treatment methods, the present invention has mild conditions and low energy consumption, which solves the technical problem of targeted recycling of high-value products of PE plastics and provides an effective strategy for realizing the economical recycling of polyethylene.

[0125] (4) ZSM-5 molecular sieve with Si / Al = 25 not only has a regular pore structure, but also has strong acid sites. The density of acid sites is generated by Al species in the catalyst composed of silicon dioxide and aluminum oxide. Therefore, we can change the surface acidity and structural characteristics of ZSM-5 molecular sieve by adjusting the solution concentration. The solution concentration range is 0.03 mol / L to 0.23 mol / L.

[0126] (5) By adjusting the surface structure of the catalyst, the experimental results showed that the yield of liquid dicarboxylic acid changed in a volcano-like manner with the acid concentration of the solution. The yield of liquid oil was the highest in the reaction time range of 4h to 14h. The catalyst used was inexpensive and widely used. It did not require ZSM-5 molecular sieve loaded with precious metals. Under specific reaction conditions, the catalytic effect and directional recovery effect were excellent.

[0127] (6) The reaction conditions are relatively mild. At 160°C, the reaction temperature is significantly lower than that of other existing processing technologies, and the overall energy consumption of the reaction is reduced. The high-value oil product yield of the embodiments of this application is high, and for different types of commercial-grade PE (HDPE, LDPE, LLDPE) and PP plastics, as well as actual plastics such as Yisaoguang packaging bags and SF Express packaging bags, ZSM-5 (25) molecular sieves maintain good catalytic activity, proving that the catalyst has universal catalytic performance.

[0128] (7) The use of inexpensive and stable catalysts reduces process conditions, improves the catalytic cracking reaction rate and efficiency, and yields more dicarboxylic acid after the reaction, which can meet the cost requirements for plastic catalytic conversion.

[0129] (8) The ZSM-5 molecular sieve catalyst with a silicon-to-aluminum ratio of 25, combined with a temperature of 160°C, air introduction and air pressure of 1.5MPa, and a reaction time of 4-14h, can control the acid modification concentration, atmosphere, and time, and can directionally catalytically oxidize polyolefin plastics into liquid dicarboxylic acid, and can maintain the yield at more than 70%, and can reach or exceed 94%, which is significantly superior to existing catalytic technologies.

[0130] The above description is merely a specific embodiment of this application, enabling those skilled in the art to understand or implement this application. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of this application. Therefore, this application is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features claimed herein.

Claims

1. A method for the catalytic oxidative degradation of polyolefin plastics, the method comprising: The ZSM-5 molecular sieve catalyst particles having a set Si / Al molar ratio are modified using an acid with a set molar concentration to obtain a modified ZSM-5 molecular sieve catalyst; wherein the set Si / Al molar ratio is ≤38 and greater than 0. The modified ZSM-5 molecular sieve catalyst, polyolefin plastic, and water were mixed to carry out a catalytic oxidative degradation reaction to obtain a reaction solution containing a dicarboxylic acid.

2. The method according to claim 1, characterized in that, The Si / Al molar ratio is set to be 25–38.

3. The method according to claim 1, characterized in that, The set molar concentration is 0.03 mol / L to 0.23 mol / L.

4. The method according to claim 3, characterized in that, The ratio of the volume V of the acid to the mass M of the ZSM-5 molecular sieve catalyst is (30-70):(0.2-2). If the unit of V is ml, then the unit of M is g.

5. The method according to claim 1, characterized in that, The acid is at least one of the following: inorganic acid or organic acid.

6. The method according to claim 5, characterized in that, The inorganic acid includes at least one of the following: hydrochloric acid, nitric acid, phosphoric acid; and / or, The organic acid includes at least one of the following: citric acid and oxalic acid.

7. The method according to claim 1, characterized in that, The modification process parameters include: temperature of 70℃~90℃ and time of 0.5h~1.5h.

8. The method according to claim 1, characterized in that, The process parameters for the catalytic oxidation degradation reaction include: air pressure of 1 MPa to 2 MPa, temperature of 140°C to 170°C, and time of 4 h to 14 h.

9. The method according to claim 1, characterized in that, The modified ZSM-5 molecular sieve catalyst and the polyolefin plastic are in a mass ratio of 1:4 to 2:

1.

10. The method according to claim 1, characterized in that, The polyolefin plastic includes at least one of the following: high-density polyethylene, linear low-density polyethylene, low-density polyethylene, polypropylene plastic, and finished polyolefin plastics.